1996
DOI: 10.1038/ng0696-189
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the activin receptor–like kinase 1 gene in hereditary haemorrhagic telangiectasia type 2

Abstract: Hereditary haemorrhagic telangiectasia, or Osler-Rendu-Weber (ORW) syndrome, is an autosomal dominant vascular dysplasia. So far, two loci have been demonstrated for ORW. Linkage studies established an ORW locus at chromosome 9q3; endoglin was subsequently identified as the ORW1 gene. A second locus, designated ORW2, was mapped to chromosome 12. Here we report a new 4 cM interval for ORW2 that does not overlap with any previously defined. A 1.38-Mb YAC contig spans the entire interval. It includes the activin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
683
1
20

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,041 publications
(710 citation statements)
references
References 32 publications
6
683
1
20
Order By: Relevance
“…Our results are well in accordance with previous publications on hepatic manifestations in patients with HHT. Although liver involvement was reported for a few patients with ENG mutations, (Berg et al, 2003;Harrison et al, 2003;Cymerman et al, 2003;Shovlin et al, 1997) it was much more often reported for patients carrying mutations in the ALK1 gene (Johnson et al, 1996;Piantanida et al, 1996;Berg et al, 1997;McDonald et al, 2000;Lin et al, 2001;Trembath et al, 2001;Olivieri et al, 2002;Abdalla et al, 2003a & b ;Berg et al, 2003). Liver involvement was not routinely assessed in most of these studies, since the emphasis was mainly on the genotype and not the phenotype, or the reports were on multiple family members and not on unrelated individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are well in accordance with previous publications on hepatic manifestations in patients with HHT. Although liver involvement was reported for a few patients with ENG mutations, (Berg et al, 2003;Harrison et al, 2003;Cymerman et al, 2003;Shovlin et al, 1997) it was much more often reported for patients carrying mutations in the ALK1 gene (Johnson et al, 1996;Piantanida et al, 1996;Berg et al, 1997;McDonald et al, 2000;Lin et al, 2001;Trembath et al, 2001;Olivieri et al, 2002;Abdalla et al, 2003a & b ;Berg et al, 2003). Liver involvement was not routinely assessed in most of these studies, since the emphasis was mainly on the genotype and not the phenotype, or the reports were on multiple family members and not on unrelated individuals.…”
Section: Resultsmentioning
confidence: 99%
“…(Shovlin, 1997). Disease-causing mutations had been identified in both the endoglin (ENG, MIM# 131195) gene (McAllister et al, 1994) on chromosome 9 (HHT type 1) and in the activin receptor-like kinase (ALK1, also designated ACVRL1, MIM# 601284) gene (Johnson et al, 1996) on chromosome 12 (HHT type 2). The presence of two disease loci provided the rationale for genotype/phenotype studies of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial and smooth muscle cells express all the examined type I and II receptors of TGF-b superfamily, indicating that multiple members of TGF-b superfamily may contribute to the maintenance or remodeling of vessel structure (Yang et al 1990;McAllister et al 1994;Dickson et al 1995;Johnson et al 1996). At present, ALK-1 is an orphan receptor.…”
Section: Discussionmentioning
confidence: 99%
“…However, the structure of ALK-1 is very similar to those of the other type I receptors, which suggests that it is a functioning receptor for certain TGF-b superfamily member(s). The mutation of ALK-1 causes hereditary haemorrhagic telangiectasia (type 2), and the mutation of endoglin (TGF-b receptor that modulates TGF-b signaling) causes a similar disease [hereditary haemorrhagic telangiectasia (type 1)] (McAllister et al 1994;Johnson et al 1996). This evidence suggests that ALK-1 acts to preserve the integrity of the vascular structure.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 µl of RNA from each sample (4 µg) were retro-transcribed using 200 U of MMLV-RT (Promega, Madison WI, USA), 1 µl of Random primers (Promega, Madison WI, USA) and 20 U of RNAsin RNAse Inhibitors (Promega, Madison WI, USA). The cDNA was amplified using 3.5 U of Taq Expand Long Template PCR System (Roche Diagnostic, Germany), Taq Expand Long Template Buffer 2 (Roche Diagnostic GmbH, Mannheim, Germany), and exonic primers ALK1cDNA4F and ALK1cDNA8R (Johnson et al, 1996). Bands were visualized on both polyacrylamide and agarose gel, eluted using QIAquick Gel extraction kit (QIAGEN) and cloned in a TOPOPCR2.1 TA-cloning system (Invitrogen Inc, USA).…”
Section: Mutation Analysismentioning
confidence: 99%